2020
DOI: 10.1177/2516043520960572
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of the daily ward round in a Plastic Surgery unit by adapting the SAFE Ward Round Tool of the Royal College of Surgeons of Edinburgh

Abstract: Aim Our goal was to audit the quality of the ward round documentation in our Plastic Surgery department by using the SAFE Ward Round Tool of the RCS Edinburgh’s as a reference standard, and to create an in-house pro-forma based on results and discussion. Method An initial cycle based on the SAFE Tool was undertaken with prospective audit of individual daily ward round entries. A sticker pro forma was introduced and re-audit was done using the same criteria. Based on results and discussion, the pro-forma was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The database search yielded a total of 3362 results, from which a total of 28 studies were included in the qualitative synthesis (Fig. 1) [3, 5, 9, 12–14, 21, 26–46].…”
Section: Resultsmentioning
confidence: 99%
“…The database search yielded a total of 3362 results, from which a total of 28 studies were included in the qualitative synthesis (Fig. 1) [3, 5, 9, 12–14, 21, 26–46].…”
Section: Resultsmentioning
confidence: 99%
“…Koumoullis and colleagues audited the quality of ward round documentation in a Scottish Plastic Surgery department using the SAFE Ward Round Tool. 14 They found that implementation produced measurable and sustained improvements in daily ward round practice.…”
mentioning
confidence: 99%